The construction of the eukaryotic expression plasmid pcDNA3.1/azurin and the increased apoptosis of U2OS cells transfected with it - Ye, Zhaoming (Cell Mol Biol Lett, 2007)
In our previous study, we demonstrated that azurin could selectively trigger apoptosis in human osteosarcoma cell line U2OS cells. However, the rate of apoptosis (35.8 ± 3.2%) is not very high, and azurin is too expensive to obtain readily. To solve these problems, we constructed a eukaryotic expression plasmid containing the azurin gene with an influenza virus haemagglutinin 9 peptide HA epitope tag, and transfected the recombinant plasmid pcDNA3.1(+)/azurin into U2OS cells. RT-PCR and Western blot analysis validated the successful transfection and the expression of the azurin-HA protein. Conspicuous apoptosis of the transfected cells was detected by flow cytometry (FCM) and the DNA ladder test. The apoptosis rate reached 64.3 ± 13.1%. The transcriptional levels of the Bax and p53 genes increased significantly in U2OS cells transfected with pcDNA3.1(+)/azurin, but the Bcl-2 mRNA level decreased. There was no difference in the levels of Bcl-xl mRNA and Survivin mRNA. We propose that the transfection of the recombinant plasmid pcDNA3.1(+)/azurin can significantly induce apoptosis in U2OS cells. This is closely associated with the up-regulation of the transcriptional level of the Bax and p53 genes, and the down-regulation of that of the Bcl-2 gene.